(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Communities seek to achieve the economic growth through the optimal use of resources. The human resource is considered the most important of those resources where the insurance institutions take the larger role in the protection of this resource and reducing the impact caused by dangers realization that endures. The general Iraqi insurance company is considered the leading in the field of life insurance since it was founded, and until now. This research is based on an analyzing the relation between premiums and compensations of life insurance, for individual and the group insurance, and a reality of the life insurance in the general Iraqi insurance company through a comparison between the insurance types, the individual and the group and followed procedures for marketing life insurance documents, in addition to the characteristics of each type. Then, conduct a comparative analysis study for the data of these two types of life insurance for the period 1999 – 2008 in terms of growth rates in the premium and the compensations, and finding of a correlation coefficient compensation and premium of both types, and the analysis of the difference between two arithmetic means for the premium and the compensations for the period of study using the SPSS. The researchers have relied on the annual report of the general Iraqi insurance company for the period 1999 – 2008 as a source of the applied data for the research.